Pengembangan Media Pembelajaran Permainan Kasdrum Untuk Peserta Didik Kelas V SD Negeri Sengi 01 - Firman Efendi; Ranu Baskora Aji Putra; Agung Wahyudi; Roas Irsyada (Indonesian Journal for Physical Education and Sport, 2024)
The aim of this research is to produce kasdrum games for elementary schools and test theeffectiveness of this model. This research method is development research. Data collectionwas carried out by interviews, document analysis and questionnaires obtained from expertevaluations and the results of filling out questionnaires by 19 class V students. The dataanalysis techniques used were qualitative data analysis techniques of interview transcriptsand document analysis results, quantitative data analysis techniques, participant needsanalysis questionnaires. education, and quantitative data analysis techniques, product designvalidation questionnaires and product validation. From the test results of material expertsand supporting teachers, analysis results were obtained at 3.4 with very good criteria, resultsfrom material experts, design experts and supporting teachers obtained product analysisresults at 3.5 with very good criteria. Meanwhile, from the student response test from 19students, data of 93.53% was obtained with very interesting criteria. Based on these results,it can be concluded that the "kasdrum" game development model can be used in PhysicalEducation learning for fifth grade students at SDN Sengi 01. Suggestions for PhysicalEducation teachers are that the poison ball development game can be used as an alternativeeducational learning model that is effective and fun and can be used in elementary schools